The Management of Sleep Disturbances in Patients with Schizophrenia: A Case Series - Vanek, Jakub; Prasko, Jan; Genzor, Samuel; Mizera, Jan (Psychology research and behavior management, 2022)
Patients with schizophrenia commonly encounter a variety of sleep disorders. Disturbed sleep can be found in 30-80% of patients, depending on the degree of psychotic symptomatology. Difficulty falling asleep, maintaining, or achieving restful sleep is associated with symptom severity and has been reported as a prodromal symptom of psychotic relapse. Although some sleep disorders improve with antipsychotic treatment, in many cases, even during disease remission, sleep continues to be fragmented, or even different pathophysiological mechanism is causing sleep disruption. Moreover, it may be complicated if the patient needs specific treatment, such as positive airway pressure (PAP) therapy, due to sleep-disordered breathing. The article presents case reports of patients with schizophrenia with sleep disturbances. As presented in our case reports, cognitive behavioral therapy seems effective in treating comorbid insomnia, even in patients with schizophrenia. The second and third case reports emphasise the need for broader clinical considerations, a cross-diagnostic approach, and cooperation in care for patients with severe mental disorders.
Keywords: symptomatology; actigraphy; sleep; antipsychotics; polysomnography; hypnotics; NREM sleep; schizophrenia; REM sleep; cognitive behavioral therapy